Basic Psychological Needs Satisfaction and Learning Enjoyment In Asynchronous Learning: Evidence From University Students - Putri Sukma Deri; Izzanil Hidayati; Silvi Juwita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
Asynchronous online learning has become a widely used learning mode in higher education after the Covid-19 pandemic. It is important to understand the psychological factors that contribute to students' enjoyment of the asynchronous learning process. One approach that can be used is Self-Determination Theory (SDT), which provides a framework for understanding the motivational antecedents of emotions by meeting basic psychological needs such as autonomy, competence, and relatedness. This study was conducted on 205 active students who had experienced asynchronous learning. Data collection was conducted using the Activity-Feeling States (AFS) to measure the fulfillment of psychological needs in students and the enjoyment subscale of the Achievement Emotions Questionnaire (AEQ) to determine students' perceived enjoyment. The results of the multiple linear regression showed significant results (p